Awareness of Traumatic Dental Injuries and Impact of Educational Intervention Among Croatian Soccer Coaches and Players - Dina Bursać; Lovro Marinović; Marta Horvat; Kristina Goršeta (Dentistry Journal)
Background/Objectives: This study aimed to assess the knowledge of dental injuries in both soccer coaches and players, as well as the impact of educational intervention on coaches and the prevalence of traumatic dental injuries and mouthguard usage among soccer players. Methods: The study involved 94 male soccer players (median age 18, IQR: 12–19) and 39 coaches. Data were collected through questionnaires covering age, gender, years of experience, injury history, mouthguard use, and knowledge of tooth rescue kits and tooth repositioning. Results: Of the players, 34 (36.2%) experienced orofacial injuries during soccer, while only 7 (7.4%) used mouthguards. Reasons for not using mouthguards included discomfort (26.1%), belief they are unnecessary (26.1%), and difficulty purchasing them (8.0%). Among coaches, 24 (61.5%) reported handling dental injuries during training, including crown fractures (41.7%), tooth avulsions (33.3%), and tooth luxations (25.0%). Only four (10.3%) coaches personally used mouthguards. Conclusions: The study identified a significant lack of knowledge about dental injuries and limited use of mouthguards among Croatian soccer players. Coaches, while influential in athlete development, should also focus on injury prevention, including dental trauma.